Impacts of the quarter dividend announcement on the stock price study on consumer product industries / Muhammad Ihsan Abd Rahim - Abd Rahim, Muhammad Ihsan (2018)
In Malaysia, people start to actively involve themselves in investment and stock trading. This is because people realise that they can make a good amount of money when invest in stock. To gain profit in stock price, Investor need to know the correct indicator on predicting the movement of the stock price. The lack of the understanding on the factor that effect the stock price can cause the investor to experience loss on their investment. They need to consider the factor which can help the investor on forecasting the stock price. To solve this problem, this research focus on the effect of the quarter dividend announcement on the stock price. The variables that were chosen from the quarter dividend announcement are the companies' revenue, profit before tax, net profit, earnings per share and dividend. By using these variables, the effectiveness of the quarter dividend announcement on the stock price can be examined. This study can determine which factor that can influence the stock price. This result can help the investor in forecasting the movement of the stock price and can choose the best stock that can give them the most profit. The other researcher can use this research as their reference. This paper can enlighten their thinking on making further research and explore new information on variables that affect the price of the stock.